Utilization Of Vermiwash As Biopesticide In The Management Of Pod Borer, Helicoverpa Armigera (Hubner), In Chickpea (Cicer Arietinum L.) (Applied Biological Research, 2018)
Natural products in insect pest management programs have gained recognition  due to environmental pollution, pest resistance and resurgence caused by  indiscriminate use of synthetic pesticides. An attempt was made to find out  ecofriendly pest management strategies by utilizing locally available botanical  and vermiwash extracts during rabi, 2015-16 at College of Agriculture  Vijayapur (India), to assess compatibility between vermiwash and botanicals  ant their effect on pod borer, Helicoverpa armigera (Hubner), in chickpea  ecosystem. The botanical extracts, viz. Parthenium hysterophorus and Vitex  nigunda, neem seed kernel extract (NSKE) and garlic-chilli kerosine extract  (GCKE) were evaluated alone or in combination with vermiwash (10%.). The results revealed that the plots treated with vermiwash @ 10% + NSKE @ 5%  or vermiwash @ 10% + GCKE @ 3% recorded less number of eggs and larva  of H. armigera. Further, in these treatments less pod damage and high grain  yields were observed. Vermiwash treatment alone recorded highest number of  eggs, larvae and pod damage as compared to other treatment-combination but  was superior in number of natural enemy, Campoletis chloridae. Further, grain  yield in this treatment was inferior to botanical treatments but significantly  superior over untreated control, followed by Vitex nigunda (5%).
Keywords: Botanical extracts; chickpea; Helicoverpa armigera; vermiwash